Electrode material based on MOF (at) COF / BC and application of electrode material in wastewater treatment

By developing an electrode material based on MOF@COF/BC, and using electrocatalytic activation of persulfate to degrade OFX wastewater, the problem of difficulty in degrading OFX in the prior art was solved, and efficient and stable OFX degradation effect was achieved.

CN119873966AActive Publication Date: 2025-04-25SHANDONG AGRICULTURAL UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510070078.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently degrade the residual offloxacin (OFX) in water, and its long-term residence and high biological activity pose a threat to ecosystems and human health.

Method used

A MOF@COF/BC-based electrode material was developed to degrade OFX wastewater by electrocatalyzing persulfate (PMS), thereby improving the degradation efficiency of OFX wastewater.

Benefits of technology

The electrode material has excellent electrochemical properties, high catalytic activity and stable structure, which can significantly improve the degradation rate of OFX to more than 99.12%, and has good cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873966A_ABST
    Figure CN119873966A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode material based on MOF (at) COF / BC and application of the electrode material in wastewater treatment, and belongs to the technical field of wastewater treatment. The electrode material provided by the invention is prepared by the following method: dissolving NH2-MIL101 (Fe), melamine and molybdenum phthalocyanine in dimethyl sulfoxide, reacting at 160-200 DEG C for 10-14 hours, collecting precipitates after the reaction, washing and drying to prepare NH2-MIL101 (Fe) (at) Mel-MoPc; the biochar and NH2-MIL101 (Fe) coated Mel-MoPc are mixed in deionized water, ultrasonic treatment is carried out for 8-12 min, stirring is carried out for 10-14 h, then centrifugation is carried out, precipitates are collected, washing and drying are carried out, and the electrode material is prepared. The invention develops and designs a novel electrode material, and the novel electrode material is used for degrading OFX wastewater by electrocatalytically activating peroxymonosulfate, so that the degradation efficiency of the OFX wastewater is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wastewater treatment, and in particular to an electrode material based on MOF@COF / BC and application thereof in wastewater treatment. Background Art

[0002] Ofloxacin (OFX) is a common quinolone antibiotic widely used in production fields such as medicine, animal husbandry and aquaculture. Its structure is stable and its degradation time in the environment is long, which makes it stay in the environment for a long time and has high biological activity. Most of them are not biodegradable and are often detected in wastewater, surface water, and even drinking water. Excessive OFX residues in water can cause a series of problems, including drug-resistant bacteria and chronic toxic effects, and accumulate in the human body through the food chain, thus causing harm to the ecosystem and human health. Therefore, there is an urgent need for effective methods to degrade residual OFX in water.

[0003] At present, the main methods for degrading wastewater containing antibiotics include: photocatalysis, ozone catalysis, Fenton catalysis and advanced oxidation technologies such as activated persulfate. Among them, activated persulfate has the advantages of strong oxidizing ability, fast reaction and low energy consumption. It is the main method currently used to degrade antibiotic wastewater.

[0004] The advanced oxidation technology based on persulfate is to produce a large amount of active substances by activating persulfate, and then undergo a series of redox reactions with the refractory organic matter in the water to achieve the degradation of refractory organic pollutants in the wastewater. Common methods for activating persulfate mainly include thermal activation, ultrasonic activation, photoactivation, transition metal and its oxide activation, and electrochemical activation methods. Among them, the advanced oxidation technology of electrochemically activated persulfate is that the persulfate obtains electrons at the cathode and is activated. Using a stable anode, the OO bond of the persulfate breaks under the electron bombardment provided by the cathode, thereby generating sulfate radicals with high redox potential. The key to electrochemically activating persulfate lies in the selection of electrode materials. The electrode material is the core of the electrochemical system, which is closely related to the electron transfer rate of the reaction system, thereby affecting the activation efficiency of persulfate. Therefore, the development of new electrode materials for activating persulfate is still a hot spot and difficulty in current research. Summary of the invention

[0005] In view of the above prior art, the purpose of the present invention is to provide an electrode material based on MOF@COF / BC and its application in wastewater treatment. The present invention develops and designs a new type of electrode material, which is used for electrocatalytic activation of peroxymonosulfate (PMS) to degrade OFX wastewater, greatly improving the degradation efficiency of OFX wastewater.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect of the present invention, an electrode material based on MOF@COF / BC is provided, which is prepared by the following method:

[0008] (1) NH 2 -MIL101(Fe), melamine and molybdenum phthalocyanine were dissolved in dimethyl sulfoxide (DMSO) and reacted at 160-200°C for 10-14h. After the reaction, the precipitate was collected, washed and dried to prepare NH 2 -MIL101(Fe)@Mel-MoPc;

[0009] (2) Biochar (BC) and NH 2 -MIL101(Fe)@Mel-MoPc was mixed in deionized water, ultrasonically treated for 8-12 min, stirred for 10-14 h, and then the precipitate was collected by centrifugation, washed and dried to prepare the electrode material (MIL101(Fe)@Mel-MoPc / BC).

[0010] Preferably, in step (1), NH 2 -The mass ratio of MIL101(Fe), melamine and molybdenum phthalocyanine added is (0.33-1.5):(0.165-0.33):(0.335-0.67).

[0011] More preferably, NH 2 -The mass ratio of MIL101(Fe), melamine and molybdenum phthalocyanine added was 0.5:0.33:0.67.

[0012] Preferably, in step (2), the biochar is prepared by the following method:

[0013] The rice husk was placed in a tube furnace and heated to 500 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and maintained for 2 h.

[0014] Preferably, in step (2), biochar and NH 2 -The mass ratio of MIL101(Fe)@Mel-MoPc is 2:1.

[0015] The present invention utilizes melamine and molybdenum phthalocyanine to grow in situ on MIL101 (Fe) to form Mel-MoPc with COF structure to obtain MOF@COF material; then the MOF@COF material is loaded on biochar (BC) to prepare an electrode material based on MOF@COF / BC. The electrode material prepared by the present invention has superior electrochemical performance, high catalytic activity and more stable structure.

[0016] The second aspect of the present invention provides the use of the above electrode material in the following (1) or (2):

[0017] (1) Activated persulfate;

[0018] (2) Degradation of antibiotics.

[0019] In the above application, preferably, the antibiotic is ofloxacin.

[0020] The third aspect of the present invention provides an electrochemical system for degrading ofloxacin, comprising: an anode, a cathode and an electrolyte;

[0021] The anode is a graphite electrode;

[0022] The cathode is prepared by the following method:

[0023] The electrode material is mixed with carbon black, polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) are added and ground into a paste, and then coated on both sides of graphite paper to prepare a cathode;

[0024] The electrolyte is 50 mM Na 2 SO 4 .

[0025] Preferably, the electrode material and carbon black are mixed in a mass ratio of 2:1.

[0026] A fourth aspect of the present invention provides a method for degrading ofloxacin in wastewater using the above electrochemical system, comprising the following steps:

[0027] The cathode and the anode are installed in an electrolytic cell filled with electrolyte, wastewater to be treated is added into the electrolytic cell, PMS is added, the pH of the system is adjusted to 7, the current is controlled to be 300-900mA, and ofloxacin in the wastewater is degraded.

[0028] Preferably, PMS is added to a final concentration of 0.5 mM.

[0029] Beneficial effects of the present invention:

[0030] The present invention prepares an electrode material based on MOF@COF / BC for the first time, wherein:

[0031] MIL101(Fe) has the characteristics of huge unit cell volume, large specific surface area, high porosity, excellent thermal stability and numerous unsaturated active sites. Its active Fe(II) / Fe(III) valence state conversion and excellent ligand-metal electron transfer ability in the catalytic process are conducive to the activation of PMS. Melamine is a monomer that constitutes COF. Melamine contains a rigid triazine ring with three functional amino groups, which can provide more active sites. Phthalocyanine in molybdenum phthalocyanine has a wide range of 18 electron conjugated systems, which has obvious advantages as a catalyst active center on COF. By molybdenizing its central cavity, a Mo-N4 Molybdenum phthalocyanine with a structure is used as an efficient active site for activating PMS. Biochar has a porous structure, rich functional groups, and a large specific surface area. It can be used as a catalyst carrier and provides a large number of active functional groups (such as C=O) to promote the reaction process of active oxygen formation. (C=O+S 2 O 8 2 -→CO + +SO 4 2- +SO 4 .- 、C=O+S 2 O 8 2 -→CO + +SO 4 2- +O 2 .- ).

[0032] However, the conductivity of MIL101(Fe) alone is poor, and Mel-MoPc has disadvantages such as poor crystallinity. The present invention grows Mel-MoPc in situ on MIL101(Fe), and assembles the two in a system to form a MIL101(Fe)@Mel-MoPc composite material with superior electrochemical performance, higher catalytic activity, and more stable structure, which can provide more active sites and channels, which is conducive to charge transfer. Then it is loaded on BC, which has the structural advantage of supporting MIL101(Fe)@Mel-MoPc, exposing more active sites and improving catalytic performance. In addition, the presence of oxygen-containing functional groups in BC allows PMS to directly or indirectly generate free radicals through electron transfer, further enhancing the activation performance of the catalyst for PMS. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : SEM images of different materials, including: (a) BC, (b) NH 2 -MIL101(Fe), (c)Mel-MoPc, (d)NH 2 -MIL101(Fe)@Mel-MoPc, (e)MIL101(Fe)@Mel-MoPc / BC.

[0034] Figure 2 : XPS spectrum of MIL101(Fe)@Mel-MoPc / BC prepared in Example 1, wherein (a) is the fine spectrum of C1s, (b) is the N1s spectrum, (c) is the Fe 2p spectrum, and (d) is the fine spectrum of Mo 3d.

[0035] Figure 3: CV diagrams of different electrode materials; wherein, 1:2 in (a) represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 1, 1:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 2, 1:3 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 3, 2:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 4, and 3:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 5. BC; 1:2 in (b) represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 1, 1:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 6, 1:3 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 7, 2:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 8, 3:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 9, and 1:0 represents NH 2 -MIL101(Fe)@Mel-MoPc, 0:1 represents BC alone.

[0036] Figure 4 : IT diagrams of different electrode materials; wherein, 1:2 in (a) represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 1, 1:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 2, 1:3 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 3, 2:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 4, and 3:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 5. BC; 1:2 in (b) represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 1, 1:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 6, 1:3 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 7, 2:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 8, 3:1 represents MIL101(Fe)@Mel-MoPc / BC prepared in Example 9, and 1:0 represents NH 2 -MIL101(Fe)@Mel-MoPc, 0:1 represents BC alone.

[0037] Figure 5 : The existence of active species in the electrocatalytic activation of PMS to degrade OFX system was detected by electron paramagnetic resonance (EPR).

[0038] Figure 6 :Effects of different current conditions on OFX degradation.

[0039] Figure 7 : Results of the cycle stability investigation of electrode materials.

[0040] Figure 8 : Degradation effect of different electrode materials on OFX. DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0043] The test materials used in the examples and comparative examples of the present invention without specific description are all conventional test materials in the art and can be purchased through commercial channels. Among them:

[0044] NH 2 -MIL101(Fe) was prepared by the following method:

[0045] 0.412 g of 2-aminoterephthalic acid and 1.35 g of ferric chloride hexahydrate were added to 30 mL of N,N-dimethylformamide (DMF) solution, stirred and mixed evenly, and the mixture was poured into a reactor, reacted at 110 ° C for 20 hours, cooled to room temperature, and centrifuged at 4500 rpm for 2 minutes to obtain NH 2 -MIL101(Fe), washed with DMF solution and ethanol, dried under vacuum at 60°C, and ground for later use.

[0046] Molybdenum phthalocyanine is prepared by the following method:

[0047] 3.8 g of 4-nitrophthalonitrile, 9.6 g of molybdenum chloride and 9.6 g of urea were ground, and 150 mg of ammonium molybdate was used as a catalyst. The mixture was heated at 160°C for 5 h, and the unreacted substances were removed by washing with 100 mL of 1 M hydrochloric acid at 90°C. The unreacted substances were further washed with 100 mL of 1 M NaOH solution until the pH was neutral. The mixture was washed with water, filtered and dried in vacuo to prepare molybdenum phthalocyanine.

[0048] Biochar (BC) is prepared by the following method:

[0049] The rice husk biomass was placed in a tubular furnace and heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2 hours. The product after the reaction was ground through a 100-mesh sieve and soaked in a 1mol / L hydrochloric acid solution for 24 hours (solid-liquid ratio 1g:100mL) to remove impurities such as ash, then washed with deionized water until neutral, and dried at 105°C to prepare biochar.

[0050] Example 1: Preparation of electrode materials based on MOF@COF / BC

[0051] 1. NH 2 - Preparation of MIL101(Fe)@Mel-MoPc:

[0052] 0.5 g NH 2 -MIL101(Fe), 0.33 g melamine and 0.67 g molybdenum phthalocyanine were dissolved in a reactor containing 23 mL DMSO to obtain a clear solution, which was reacted at 180 °C for 12 hours. After the reactor was cooled to room temperature, a white precipitate was collected and washed with excess dichloromethane, acetone, ethanol and distilled water to remove unreacted precursor materials and possible residual solvents in the mixture, and finally dried in an oven at 70 °C to prepare NH 2 -MIL101(Fe)@Mel-MoPc.

[0053] 2. Preparation of MIL101(Fe)@Mel-MoPc / BC:

[0054] NH 2 -MIL101(Fe)@Mel-MoPc and BC were mixed in deionized water at a mass ratio of 1:2, ultrasonically treated (ultrasonic power 500W) for 10min, and stirred for 12h. The mixture was then centrifuged at 10000rpm, the precipitate was collected, washed with ethanol, and dried at 60℃ for 24h to obtain MIL101(Fe)@Mel-MoPc / BC.

[0055] Embodiment 2:

[0056] The difference from Example 1 is that 1g NH 2 -MIL101(Fe), 0.33 g melamine and 0.67 g molybdenum phthalocyanine were dissolved in a reaction kettle filled with 23 mL DMSO, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0057] Embodiment 3:

[0058] The difference from Example 1 is that 0.33 g NH 2-MIL101(Fe), 0.33 g melamine and 0.67 g molybdenum phthalocyanine were dissolved in a reaction kettle filled with 23 mL DMSO, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0059] Embodiment 4:

[0060] The difference from Example 1 is that 1g NH 2 -MIL101(Fe), 0.165 g melamine and 0.335 g molybdenum phthalocyanine were dissolved in a reaction kettle filled with 23 mL DMSO, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0061] Embodiment 5:

[0062] The difference from Example 1 is that 1.5 g NH 2 -MIL101(Fe), 0.165 g melamine and 0.335 g molybdenum phthalocyanine were dissolved in a reaction kettle filled with 23 mL DMSO, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0063] Embodiment 6:

[0064] The difference from Example 1 is that NH 2 -MIL101(Fe)@Mel-MoPc and BC were mixed in deionized water at a mass ratio of 1:1, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0065] Embodiment 7:

[0066] The difference from Example 1 is that NH 2 -MIL101(Fe)@Mel-MoPc and BC were mixed in deionized water at a mass ratio of 1:3, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0067] Embodiment 8:

[0068] The difference from Example 1 is that NH 2 -MIL101(Fe)@Mel-MoPc and BC were mixed in deionized water at a mass ratio of 2:1, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0069] Embodiment 9:

[0070] The difference from Example 1 is that NH 2 -MIL101(Fe)@Mel-MoPc and BC were mixed in deionized water at a mass ratio of 3:1, and the other reaction conditions were the same as those in Example 1 to prepare MIL101(Fe)@Mel-MoPc / BC.

[0071] Comparative Example 1:

[0072] 0.33g of melamine and 0.67g of molybdenum phthalocyanine were dissolved in a reactor containing 23mL of DMSO to obtain a clear solution, which was reacted at 180°C for 12 hours. The white precipitate was collected after the reactor was cooled to room temperature and washed with excess dichloromethane, acetone, ethanol and distilled water to remove the unreacted precursor material and possible residual solvent in the mixture. Finally, it was placed in an oven at 70°C for drying to prepare Mel-MoPc.

[0073] Comparative Example 2:

[0074] NH 2 -MIL101(Fe) and BC were mixed in deionized water at a mass ratio of 1:2, ultrasonically treated (ultrasonic power 500W) for 10 minutes, and stirred for 12 hours. The mixture was then centrifuged at 10000 rpm, the precipitate was collected, washed with ethanol, and dried at 60°C for 24 hours to obtain MIL101(Fe) / BC.

[0075] Comparative Example 3:

[0076] Mel-MoPc and BC prepared in Comparative Example 1 were mixed in deionized water at a mass ratio of 1:2, ultrasonically treated (ultrasonic power 500 W) for 10 min, and stirred for 12 h. The mixture was then centrifuged at 10000 rpm, the precipitate was collected, washed with ethanol, and dried at 60° C. for 24 h to obtain Mel-MoPc / BC.

[0077] Test Example 1:

[0078] The NH used in the present invention 2 -MIL101(Fe), BC, NH in Example 1 2 -MIL101(Fe)@Mel-MoPc, MIL101(Fe)@Mel-MoPc / BC, and Mel-MoPc prepared in Comparative Example 1 were analyzed by scanning electron microscopy.

[0079] Its SEM is Figure 1 As shown by Figure 1 It can be seen that the surface of biochar BC is rough and has a rich pore structure ( Figure 1 a); NH 2 -MIL101(Fe) is a typical hexagonal microspindle morphology ( Figure 1b) Mel-MoPc nanoparticles with surface agglomeration ( Figure 1 c). Figure 1 (d) NH 2 -MIL101(Fe)@Mel-MoPc morphology. It can be seen that Mel-MoPc nanoparticles are dispersed in NH 2 -MIL101(Fe) surface, NH 2 -MIL101(Fe) uniformly packed. Figure 1 e indicates NH 2 -MIL101(Fe)@Mel-MoPc was loaded onto the rough BC surface, demonstrating the successful synthesis of MIL101(Fe)@Mel-MoPc / BC.

[0080] XPS analysis was performed on MIL101(Fe)@Mel-MoPc / BC prepared in Example 1 of the present invention. The results are as follows: Figure 2 shown. Figure 2 (a) is the fine spectrum of C1s, where 287.6 eV, 286 eV, 285.2 eV, and 284.3 eV correspond to C=O, CC / CN, C=N, and CC, respectively, which can effectively promote the formation of active oxygen during the reaction. The formation of C=N imine covalent bond indicates that MOF@COF is effectively synthesized, making it stable, which is beneficial to the charge transfer and the improvement of catalytic performance. Figure 2 (b) The peak at 399.4 eV in the N 1s spectrum is the Mo-N bond, indicating that the Mo-N 4 The presence of provides an active site for the reaction, indicating that electron transfer occurs between the metal and the N atom. The peak at 400.1 eV is attributed to -NH 2 , 400.6eV and 711.7eV correspond to graphite-N and pyrrole-N, respectively. Electroactivated pyrrole-N can provide abundant active sites and generate more active species. Figure 2 As shown in (c), 724.6eV and 711.7eV correspond to Fe 3+ 2p 3 / 2 and 2p 1 / 2 , Fe 2+ The characteristic peaks of are located at 717.5eV and 709.4eV, indicating the presence of Fe 2+ / Fe 3+ The redox cycle promotes the activation of PMS. The peak at 714.4 eV is Fe-N, which can provide excellent active sites and improve catalytic performance. The peak at 533.4 eV corresponds to the Fe-O bond, and the peaks at 532.8 eV and 535.1 eV belong to the Mo=O bond and -OH, respectively. The fine spectrum of Mo 3d is shown in Figure 2. Figure 2(d) shows that the peaks at 229.7 eV and 225.1 eV correspond to the Mo-C bond and Mo 3+ , the two peaks at 231.8eV and 227.6eV belong to Mo 4+ Mo 3d 3 / 2 and Mo 3d 5 / 2 The two peaks at 235.3eV and 233.8eV belong to Mo 6+ , 232.1eV and 228.7eV are attributed to Mo 5+ , indicating the presence of Mo 3+ / Mo 4+ / Mo 5+ / Mo 6+ The redox cycle between the two promoted the generation of active species. The XPS results further proved the successful preparation of MIL101(Fe)@Mel-MoPc / BC. In addition, the formation of MNC structure between Fe, Mo, C and N was more conducive to electron transfer, which further improved the electrocatalytic performance of the material.

[0081] Test Example 2:

[0082] The redox ability and electron transfer ability of MIL101(Fe)@Mel-MoPc / BC prepared in Examples 1 to 9 of the present invention were investigated, as follows:

[0083] 1. Cyclic voltammetry (CV):

[0084] The cyclic voltammetry (CV) test results show that the peak current of MIL101(Fe)@Mel-MoPc / BC prepared in Example 1 is the highest ( Figure 3 ), indicating that the catalyst prepared under this condition has stronger redox ability.

[0085] 2. Timing current test (IT):

[0086] The chronoamperometric test (IT) was performed at open circuit voltage with 50 mM Na 2 SO 4 , sampling interval is 0.1s, running time is 300s, sensitivity is 0.0001A / V, and 0.5mM PMS is added at 100s. Under open circuit voltage conditions, the current increases immediately after adding 0.5mM PMS at 100s, proving that electron transfer occurs between the material and PMS. The greater the current change, the stronger its electron transfer ability.

[0087] Depend on Figure 4 It can be seen that after adding PMS, the current change of the material prepared in Example 1 is 1.4028e -7 , while using NH alone 2-The current change of MIL101(Fe)@Mel-MoPc is 0.9022e -7 , the current change of BC alone is 0.487e -7 It is proved that the material prepared in Example 1 has the strongest electron transfer ability. 2 -The composite of MIL101(Fe)@Mel-MoPc and BC has a synergistic effect in improving the electron transfer ability of the material.

[0088] Test Example 3:

[0089] The electrode material prepared by the present invention is used to activate PMS to degrade OFX, specifically as follows:

[0090] 1. Construction of reaction system:

[0091] The electrode material and carbon black were mixed in a mass ratio of 2:1 (total amount after mixing was 10 mg), and then fully ground with 10 mg of polyvinylidene fluoride (PVDF) in a quartz mortar, followed by adding 0.3 mL of NMP, fully ultrasonicated, and drop-coated on one side of graphite paper (2 cm × 2 cm × 1 mm), and dried naturally. The other side was prepared in the same way to obtain a cathode. It was placed in a 200 mL cylindrical electrolytic cell with a graphite anode (2 cm × 2 cm × 1 mm) with a plate spacing of 2 cm; 50 mM Na 2 SO 4 As an electrolyte, a reaction system is constructed.

[0092] 2. Investigation of active substances in the electrocatalytic activation of PMS to degrade OFX system:

[0093] The electrode material MIL101(Fe)@Mel-MoPc / BC prepared in Example 1 was used to construct a reaction system according to the above method, and PMS and OFX were added to the reaction system to make the final concentration of PMS 0.5 mM, the concentration of OFX 10 mg / L, and the current was set to 300 mA.

[0094] Electron paramagnetic resonance (EPR) was used to detect the presence of active species SO in the electrocatalytic activation of PMS to degrade OFX 4 - , ·OH, ·O 2 - and 1 O 2 ; The results are as follows Figure 5 As shown, it is proved that PMS was successfully activated to generate active species for the degradation and removal of OFX.

[0095] 3. Optimization of reaction conditions:

[0096] The electrode material MIL101(Fe)@Mel-MoPc / BC prepared in Example 1 was used to construct a reaction system according to the above method. PMS and OFX were added to the reaction system to make the final concentration of PMS 0.5 mM and the concentration of OFX 10 mg / L. The currents were set to 100 mA, 300 mA, 500 mA, 700 mA and 900 mA, respectively, to investigate the effect of different current conditions on the degradation effect of OFX.

[0097] The results are as follows Figure 6 As shown in the figure, the degradation of OFX increases with the increase of current. When the current is ≥300mA, the degradation rate of OFX reaches more than 92%. In particular, when the current is set to 900mA, the OFX degradation rate is as high as 99.12%. The increase of current promotes the degradation of Fe in the catalyst. Ⅱ / Ⅲ with Mo Ⅳ / Ⅴ / Ⅵ The redox cycle improves the catalytic activity and enhances the ·OH, ·O 2 - 、SO 4 - , 1 O 2 Active species such as phospholipids and oligosaccharides are produced, thereby promoting the degradation of OFX.

[0098] 4. Cyclic stability investigation:

[0099] The electrode material MIL101(Fe)@Mel-MoPc / BC prepared in Example 1 was used to construct a reaction system according to the above method, and PMS and OFX were added to the reaction system to make the final concentration of PMS 0.5 mM and the concentration of OFX 10 mg / L. Under the same test conditions, the cathode was subjected to 9 cycle tests.

[0100] The results are as follows Figure 7 As shown, the degradation rate of OFX decreased by only 7.61% after 9 cycles, indicating that the cathode has good cycling stability.

[0101] 5. Degradation effect of different electrode materials on OFX:

[0102] The electrode material MIL101(Fe)@Mel-MoPc / BC prepared in Example 1, the electrode material MIL101(Fe) / BC prepared in Comparative Example 2, and the electrode material Mel-MoPc / BC prepared in Comparative Example 3 were respectively used to construct a reaction system according to the above method, and PMS and OFX were added to the reaction system to make the final concentration of PMS 0.5mM and the concentration of OFX 10mg / L. The current was set to 300mA. The effect of different electrode materials on the degradation effect of OFX was investigated. No electrode material was added and only PMS was added as a control.

[0103] The results are as follows Figure 8As shown, the efficiency of OFX degradation by permonosulfate alone is only 5.8%, the degradation rate of OFX degradation by MIL101(Fe) / BC activated PMS is 56.4%, the degradation rate of OFX degradation by Mel-MoPc / BC activated PMS is 30.8%, and the degradation rate of OFX degradation by MIL101(Fe)@Mel-MoPc / BC activated PMS is 92.6%. The above results prove that the electrode material prepared by the present invention can activate permonosulfate and improve its degradation effect on OFX; MIL101(Fe) and Mel-MoPc have a synergistic effect on the activation of PMS to degrade OFX.

[0104] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An electrode material based on MOF@COF / BC, characterized in that: Prepared by the following method: (1) dissolving NH2-MIL101(Fe), melamine and molybdenum phthalocyanine in dimethyl sulfoxide, reacting at 160-200° C. for 10-14 h, collecting the precipitate after the reaction, washing and drying, and preparing NH2-MIL101(Fe)@Mel-MoPc; (2) The biochar and NH2-MIL101(Fe)@Mel-MoPc were mixed in deionized water, ultrasonically treated for 8-12 min, stirred for 10-14 h, and then the precipitate was collected by centrifugation, washed, and dried to prepare the electrode material.

2. The electrode material according to claim 1, characterized in that In step (1), the mass ratio of NH2-MIL101(Fe), melamine and molybdenum phthalocyanine added is (0.33-1.5):(0.165-0.33):(0.335-0.67).

3. The electrode material according to claim 1, characterized in that In step (2), the biochar is prepared by the following method: The rice husk was placed in a tube furnace and heated to 500 °C at a heating rate of 5 °C / min under a nitrogen atmosphere and maintained for 2 h.

4. The electrode material according to claim 1, characterized in that In step (2), the mass ratio of biochar to NH2-MIL101(Fe)@Mel-MoPc is 2:

1.

5. Use of the electrode material according to any one of claims 1 to 4 in the following (1) or (2): (1) Activated persulfate; (2) Degradation of antibiotics.

6. The use according to claim 5, characterized in that: The antibiotic is ofloxacin.

7. An electrochemical system for degrading ofloxacin, characterized in that: include: Anode, cathode and electrolyte; The anode is a graphite electrode; The cathode is prepared by the following method: The electrode material according to any one of claims 1 to 4 is mixed with carbon black, polyvinylidene fluoride and N-methylpyrrolidone are added, ground into a paste, and coated on both sides of graphite paper to prepare a cathode; The electrolyte was 50 mM Na2SO4.

8. A method for degrading ofloxacin in wastewater using the electrochemical system according to claim 7, characterized in that: The following steps are involved: The cathode and the anode are installed in an electrolytic cell filled with electrolyte, wastewater to be treated is added into the electrolytic cell, PMS is added, the pH of the system is adjusted to 7, the current is controlled to be 300-900mA, and ofloxacin in the wastewater is degraded.

Citation Information

Patent Citations

  • MOFs (at) COFs catalyst with core-shell structure, preparation method of MOFs (at) COFs catalyst and application of MOFs (at) COFs catalyst in electrochemical ammonia synthesis reaction

    CN114686922A

  • Preparation and application of anode oxygen evolution catalyst with high-valence metal vanadium doped with CoFe-MOF / NF

    CN116083954A

  • Fe-N-C catalyst with double active sites as well as preparation method and application of Fe-N-C catalyst

    CN116493035A

  • Preparation method and application of MIL68 (Fe) / MoS2 composite catalyst

    CN116920952A

  • MILLIMETER-SCALE PEROXYMONOSULFATE ACTIVATOR ZSM-5-(C@Fe) AND PREPARATION METHOD AND APPLICATION THEREOF

    US20210394164A1